Sfp1 links TORC1 and cell growth regulation to the yeast SAGA‐complex component Tra1 in response to polyQ proteotoxicity. (15th March 2019) - Jiang, Yuwei; Berg, Matthew D.; Genereaux, Julie; Ahmed, Khadija; Duennwald, Martin L.; Brandl, Christopher J.; Lajoie, Patrick
Abstract : Chromatin remodeling regulates gene expression in response to the accumulation of misfolded polyQ proteins associated with Huntington's disease (HD). Tra1 is an essential component of both the SAGA/SLIK and NuA4 transcription co‐activator complexes and is linked to multiple cellular processes, including protein trafficking and signaling pathways associated with misfolded protein stress. Cells with compromised Tra1 activity display phenotypes distinct from deletions encoding components of the SAGA and NuA4 complexes, indicating a potentially unique regulatory role of Tra1 in the cellular response to protein misfolding. Here, we employed a yeast model to define how the expression of toxic polyQ expansion proteins affects Tra1 expression and function. Expression of expanded polyQ proteins mimics deletion of SAGA/NuA4 components and results in growth defects under stress conditions. Moreover, deleting genes encoding SAGA and, to a lesser extent, NuA4 components exacerbates polyQ toxicity. Also, cells carrying a mutant Tra1 allele displayed increased sensitivity to polyQ toxicity. Interestingly, expression of polyQ proteins upregulated the expression of TRA1 and other genes encoding SAGA components, revealing a feedback mechanism aimed at maintaining Tra1 and SAGA functional integrity. Moreover, deleting the TORC1 (Target of Rapamycin) effector SFP1 abolished upregulation of TRA1 upon expression of polyQ proteins. While Sfp1 is known to adjust ribosome biogenesis and cell size in response to stress, we identified a new role for Sfp1 in the control of TRA1 expression, linking TORC1 and cell growth regulation to the SAGA acetyltransferase complex during misfolded protein stress. Abstract : Proteotoxic stress disrupts trafficking and triggers transcriptional responses to cope with the accumulation of misfolded proteins. Using a yeast model of Huntington's disease, we show that cells expressing toxic polyglutamine expansions display impaired assembly of the SAGA acetyltransferase complex that regulates chromatin remodeling and gene expression during stress. This culminates in the Sfp1/TORC1‐dependent increased expression of the SAGA component TRA1 . Our data identify a new nexus that links TORC1 to the regulation of SAGA activity during loss of proteostasis.